To study the correlation between blood lactate level and neonatal hyperbilirubinemia and to predict the severity of NHB in neonates - Zhang, Gangqiang; Shao, Kun; Zhou, Yun-heng (Journal of Medical Biochemistry, 2025)
Objective: To study the correlation between blood lactate level and hyperbilirubinemia in neonates and to analyze the predictive value of blood lactate level for the severity of NHB in neonates. Methods: A total of 123 children diagnosed with Neonatal hyperbilirubinemia (NHB) admitted to the obstetrics department from October 2021 to October 2022 were selected as the NHB group, and according to the severity of the disease, they were divided into mild, moderate, and severe.  Fifty healthy neonates born in the department of obstetrics were selected as the control group.  The levels of glucose-6-phosphate dehydrogenase (G6PD), creatine kinase isoenzyme (CK-MB), β2-microglobulin (β2-MG), aspartate aminotransferase (AST), blood lactic acid and total bilirubin in serum were compared.  Pearson correlation analysis was used to analyze the correlation between blood lactate level and bilirubin level, and the ROC curve was used to determine the predictive value of blood lactate level for the severity of NHB in neonates. Results: The NHB group had significantly higher levels of AST, CK-MB, β2-MG, blood lactic acid, and total bilirubin than the NHB group (P < 0.05).  G6PD level was significantly lower (P < 0.05).  According to Pearson, blood lactic acid level was positively correlated with total bilirubin level (r = 0.604, P < 0.001).  The ROC curve showed that the AUC of blood lactic acid level in predicting the severity of NHB was 0.873, which was higher than that of total bilirubin alone (P < 0.05).Conclusions: Neonates with NHB have higher serum levels of AST, CK-MB, β2-MG, blood lactate, and total bilirubin, while lower G6PD levels.  The serum level of blood lactate is positively correlated with the total bilirubin level, which can be used to observe the severity of NHB in neonates.